(untitled) (Journal of Universal Excellence, 2026)
Research Question (RV): Older people become dependent on the help of others at different ages. The question is, how lifestyle activities during lifetime influence self-sufficiency in old age. That is why we have examined in particular the impact of heavy physical work at the workplace on the age of entering long-term care and which type of dwelling prefer older adults. Purpose: The purpose of the article is to determine whether a lifestyle - especially hard physical work - affects the age of entering long-term care and in which type of dwelling they want to be provided when they can no longer live in their own home. The findings are essential in shaping demand projections for long-term care services. Based on these, in the long run, long-term care capacities are planned, human resources are needed, and the built-in space is provided for the provision of quality care for people dependent on the help of others. Method: We surveyed 198 elderly adults, 100 residents in Slovenian homes for the elderly, and 98 users of homecare. The respondents were classified into different groups by their lifestyle and in particular, studied the type of work they performed in the active age. We used z+4 test to show there are statistically significant differences in age of entry to long term care facilities. Results: We have come up with two crucial conclusions that arduous physical work significantly affects early entry into institutional care and most of older adults do not want to receive care in their home when they come to a state that they can no longer take care of themselves. With low p-value, we can also say that most of the elderly do not want to be at home when they come to a state that they can not take care of themselves, which is contrary to the findings of the European Commission. Organisation: Workers who have performed particularly arduous work become dependent on the help of others much earlier, which is also associated with higher expenditures for long-term care. The article deals with an example of a model for evaluating the differences in the actuarial present value of these expenditures, which can be the basis for calculating the insurance premium for occupational long-term care insurance. Company: For the provision of long-term care services, the company should allocate appropriate resources or a proper share in GDP. Originality: We demonstrated how, through the knowledge of the lifestyle of the population - the impact of arduous physical work influences the age of entering long-term care. With this insight, policymakers are can better plan the development of services, facilities, human resources and care networks for older adults dependent on the help of others. Limitations/further research: Given the vulnerability of the population studied, we managed to obtain answers only from a small number of older adults. Consequently, the estimates of the parameters are worse, but the recently developed z+4 test enables a reasonably reliable assessment of the diversity of the parameters and shows the importance of the parameters in the planned systems long-term care planning is not yet evident.